Family of [0,1] Truncated Gompertz – Exponential DistributionWith Properties and Application (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the paper we are introduce a new family of continuous distribution based on [0,1]truncated gompertz-G family distribution (TGO-GD) and [0,1] Truncated Gompertz-Exponential distribution (TGO-EXPD). We are discussed as special cases: Cumulativedistribution function (CDF), probability density function (PDF), survival function (sf), hazardrate function (hrf), revers hazard rate function (rhrf), cumulative hazard rate function (chrf),the quntial function (Qf), moment generating function (M.G.F), the moments , the mean μ,the variance σ2 ,the median M, the skewness SK , the kurtosis Ku , the entropy, orderstatistics,Asymptotic behavior and maximum likelihood estimator for [0,1] TruncatedGompertz-Exponential Distribution (TGO-EXPD). We estimate of the model parameters bymaximum likelihood and we apply empirically the potentiality of the new class by means ofone real data set.